Predictive modeling for the identification of spatial distributions of benthic animal species and key ecological features across the Aegean Sea - Κουκουρουβλή, Νικολέττα (2022)
Detailed knowledge on the distribution of ecological features is crucial for their effective management and conservation. Existing information is sparse and fragmented and at the same time costly and time consuming to obtain. In this dissertation, predictive modeling was carried out, based on environmental variables, in order to produce the continuous maps of 21 animal species and key ecological features across the Aegean Sea. The predicted distribution maps provide critical information about where the ecological features are most likely to occur. The outputs of the study can be used for the development of marine spatial plans or to guide cost-effective future surveys and monitoring efforts towards areas that are presently poorly-sampled.